Development of in-vitro Propagation Protocol of Coelogyne Flaccida - Jatin (My University, 2023)
Coelogyne flaccida (family Orchidaceae) is an important ornamental plant used as a pot and cut flower plant. The present study was focused to study the development of an in-vitro protocol for the regeneration of the orchid Coelogyne flaccida from Protocorm-like Bodies. Multiplication of the germinated culture of Coelogyne flaccida was achieved on MS medium supplemented with 2.5 μM BAP. The effect of BAP and NAA with different concentrations and combinations was observed on shoot formation and PLBs formation. The maximum number of shoot (5.22 ± 0.31) were recorded on medium supplemented with 2.5 μM BAP, and the maximum number of PLBs (14.77 ± 0.96) were formed at 1 μM each of BAP and NAA after 30 days of culture. Maturation of the PLBs was attempted on basal MS medium supplemented with different concentrations of sucrose and mannitol to achieve efficient conversion of PLBs to plantlets. The highest maturation of PLBs was observed on an MS medium supplemented with 87 mM of sucrose. Matured PLBs were germinated on MS medium supplemented with BAP and GA3. The maximum germination (18.32 ±0.44) was achieved at a concentration of 0.5 μM BAP and 1μM GA3. Further, the germinated plantlets were acclimatised in vivo.
Keywords: Protocorm like bodied; In vitro propagation; Acclimatization; Orchids